Respuesta :
Answer:
Step-by-step explanation:
when you have a negative exponent, you are going to have a fraction. Example: 2^4 * 2^-4= 2^4 is 16 2^-4 is 1/16.
You get the 16 but because it was a negative exponent, the 16 goes on the bottom. 16 as a fraction is 16/1.
When you multiply 16/1 and 1/16. It comes up to 16/16 or 1.
Does this help?
Answer:
below
Step-by-step explanation:
We can use the product rule of exponents to solve [ x^y * x^z = x^y+z ].
x^4 * x^-4 = 1
x^4+(-4) = 1
x^0 = 1
1 = 1
Best of Luck!